Seroprevalence of Human Cystic Echinococcosis in Alborz Province, Central Iran in 2015 - Hadi DABAGHZADEH; Amir BAIRAMI; Eshrat Beigom KIA; Mojgan ARYAEIPOUR; Mohammad Bagher ROKNI (Tehran University of Medical Sciences, 2018)
Background: The aim of this study was to conduct a sero-epidemiological survey in Alborz Province, central Iran to detect the rate of hydatidosis in the city and nearby villages. Methods: Overall, 680 serum samples were collected from 536 male and 127 female subjects referred to different health centers of Karaj, Alborz Province, central Iran and nearby villages in 2014-15. All patients filled out a questionnaire and an informed consent. Sera were analyzed using indirect-ELISA test with AgB. Ten μg /ml antigens (Proceeded hydatid fluid), serum dilutions of 1:500 and conjugate anti-human coombs with 1:10000 dilutions were utilized to perform the test. Data analysis was conducted using SPSS software ver. 11.5. Results: Twenty-three cases (3.4%) were positive for hydatidosis by ELISA test. The prevalence of hydatidosis among females and males was 3.1% and 4.7%, respectively. The rate of the disease was significantly higher in areas where dogs were higher (P<0.05). There was no significant difference as regards age groups, sex, job, residency, and literacy. Regarding occupation, housekeepers had the highest rate of infection as 5.9%. The sero-prevalence of infection was 4.2% in bachelors and master people which showed the highest rate. As regards residency, urban life showed no significant difference with rural life (2.8% vs. 4.4%). Age group of 30-39 yr old, with 4.3% as prevalence had the highest rate of positivity (P>0.05). Conclusion: Because of the specific situation of Alborz Province, and availability of many stray dogs, obtained rate of hydatidosis shows that the authorities should be cautious to monitor the disease.